Sperm DNA integrity and reproductive toxicity of lead nitrate in adult male mice: Integridad del ADN espermático y toxicidad reproductiva del nitrato de plomo en ratones machos adultos - Vásquez-Cavero, Jonathan H. (2023)
Introduction: Lead toxicity has been linked to different diseases in humans and several evidences suggest a strong relationship with the observed damage on reproductive function in humans and rodents. Method: Mice were given a single dose of lead nitrate (NP) (50mg/kg/bw), which were euthanized seven days post-injection with the aim of evaluating sperm to come out from the seminiferous tubules and are in transit through the epididymis. Also, the TUNEL test was done to evaluate the sperm DNA fragmentation.  Results: The decrease in body weight in mice treated with LN (p <0.05), suggest a toxic systemic effect. However, the same did’n happen on the reproductive system because the weights of the testes, epididymis, prostate and seminal vesicles were not altered (p>0.05), in the same way physiological values such as sperm concentration and motility didn´t decrease with the treatment (p> 0.05). Transit and sperm maturation in the epididymis would not be affected by the LN, and because we did not observe increased sperm DNA fragmentation in the treated group (p>0.05), sperm protamination would be fulfilling its protective role on murine genetic material avoiding genotoxic damage by LN. Conclusion: The intraperitoneal administration of 50mg/kg/pc of LN for seven days does not cause systemic toxicity or effect on spermatogenesis in mice.